Social actors in the development of health institutions in Chile: 1889-1938 (Polis (Santiago), 2018)
The author argues that the creation of the National Health Service in 1952 was a landmark project of founding a new institutional health in Chile, whose formal origins seem to go back to the previous decade, and whose original draft was submitted by the Minister of Health Salvador Allende ten years earlier. He argues that the fifties are the culmination of the Chilean political system’s tolerance to the pressure and thrust of popular organizations. The article discusses the origin and transformation of health institutions, which range from the Superior Council of Public Health to the Department of Health, through the influence of welfare, and delves into the contradictions of the welfare state, until its crisis.
Keywords: sanitary institutionality; welfare state; public health; social subjects